2002
DOI: 10.1093/embo-reports/kvf160
|View full text |Cite
|
Sign up to set email alerts
|

The Methanobacterium thermoautotrophicum MCM protein can form heptameric rings

Abstract: Mini-chromosome maintenance (MCM) proteins form a conserved family found in all eukaryotes and are essential for DNA replication. They exist as heteromultimeric complexes containing as many as six different proteins. These complexes are believed to be the replicative helicases, functioning as hexameric rings at replication forks. In most archaea a single MCM protein exists. The protein from Methanobacterium thermoautotrophicum (mtMCM) has been reported to assemble into a large complex consistent with a dodecam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 39 publications
3
83
0
Order By: Relevance
“…Although the mtMCM appears to form double hexamers (10 -13), the enzymes from S. solfataricus (16), A. fulgidus, and Aeropyrum pernix (18) are hexamers. Electron micrograph reconstruction of mtMCM revealed ring-shaped hexamers (20) or heptamers (21), but no dodecamers could be observed. The observation that the M. thermautotrophicus enzyme forms only single ring structures at low concentrations (such as those used for electron microscopy) may suggest that the double hexamers are formed by nonspecific hydrophobic or ionic interactions involving the two hexamers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the mtMCM appears to form double hexamers (10 -13), the enzymes from S. solfataricus (16), A. fulgidus, and Aeropyrum pernix (18) are hexamers. Electron micrograph reconstruction of mtMCM revealed ring-shaped hexamers (20) or heptamers (21), but no dodecamers could be observed. The observation that the M. thermautotrophicus enzyme forms only single ring structures at low concentrations (such as those used for electron microscopy) may suggest that the double hexamers are formed by nonspecific hydrophobic or ionic interactions involving the two hexamers.…”
Section: Discussionmentioning
confidence: 96%
“…The crystal structure of the N-terminal portion of the mtMCM protein suggested a dodecameric structure (19). However, electron microscope reconstructions of fulllength mtMCM revealed hexameric (20) or heptameric (21) structures, but not larger multimers.…”
mentioning
confidence: 97%
“…Consistent with this notion, the Mcm10 -43 mutant allele defective in Mcm10 selfinteraction is also defective in interacting with Mcm7, a subunit of the MCM2-7 complex known to interact with Mcm10 (43). A number of studies have suggested that the MCM2-7 complex functions as a double hexameric structure (45,46). Although it is conceivable that the ϳ800-kDa Mcm10 homocomplexes may assume a similar configuration that facilitates their interactions with the MCM2-7 complex, the stoichiometry of the Mcm10 homocomplexes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…These and other observations have led to an alternative model in which the MCM complex functions like a molecular rotary pump that is tethered during S phase and uses ATP hydrolysis to spool DNA through its pore, thereby unwinding it from a distance [7]. Structural studies have confirmed that the central pore of the MCM heterohexamer is large enough to accommodate the DNA double helix [8,9].…”
Section: Role Of MCM Proteins In Limiting Dna Replication To Once Permentioning
confidence: 99%